2022
DOI: 10.3389/fneur.2022.960454
|View full text |Cite
|
Sign up to set email alerts
|

EEG biomarkers for the diagnosis and treatment of infantile spasms

Abstract: Early diagnosis and treatment are critical for young children with infantile spasms (IS), as this maximizes the possibility of the best possible child-specific outcome. However, there are major barriers to achieving this, including high rates of misdiagnosis or failure to recognize the seizures, medication failure, and relapse. There are currently no validated tools to aid clinicians in assessing objective diagnostic criteria, predicting or measuring medication response, or predicting the likelihood of relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 85 publications
2
12
0
Order By: Relevance
“…Fig 7 compares the distribution of EEG power (absolute broadband power and relative delta frequency) in sleep without epileptiform spikes versus sleep with epileptiform spikes. These findings are concordant with prior studies [ 26 , 27 ] that showed an increase in both these metrics for individuals with epilepsy.…”
Section: Resultssupporting
confidence: 93%
“…Fig 7 compares the distribution of EEG power (absolute broadband power and relative delta frequency) in sleep without epileptiform spikes versus sleep with epileptiform spikes. These findings are concordant with prior studies [ 26 , 27 ] that showed an increase in both these metrics for individuals with epilepsy.…”
Section: Resultssupporting
confidence: 93%
“…Overall, we have demonstrated that coherence‐based networks can be constructed using EEG signals in the IESS population. In the future, understanding networks through connectivity and hub localization can be applied clinically to assess treatment options, 41 such as localizing the epileptic zone in pre‐surgical planning, 42 identifying the epileptic network for neuromodulation therapy, 43 or as a marker for treatment response. 44 …”
Section: Discussionmentioning
confidence: 99%
“… 28 , 30 , 62 Many studies have shown that different centrality measures can quantify epileptic networks within standard EEG to be potential biomarkers for epileptic tissue. 40 , 45 , 46 , 63 , 64 Similar analyses in the context of HFOs are also promising, as analysing the connectivity of EEG in the HFO frequencies or HFOs themselves shows correlation with patient outcome or can improve specificity to epilepsy. 31-36 However, network analysis with HFOs is challenging because some channels have few events, and most of the detected events on one channel are not detected on neighbouring channels even when there is a clear network discharge—which is precisely the data that are most important to analyse the network (e.g.…”
Section: Discussionmentioning
confidence: 99%